Calibration of Residual Current Device (RCD) Testers. Issue 4 (3rd December 2018) - Yang, Steven; Chau, Y. C.
Abstract: Residual current devices (RCDs) are commonly used in low voltage electric power systems, including our households, as protective devices against electric shock. They monitor the balancing current between the live and neutral terminals and will trigger the relay to disconnect the load from the power line when a leakage current is detected. The functional test of RCDs may be performed by an RCD tester, which emulates a residual leakage current between the live and the earth terminals, and to measure the tripping time of RCDs under different defined test scenarios. At the Standards and Calibration Laboratory (SCL), a traceable RCD tester calibration system was developed in-house. With the application of digital sampling techniques, all the major functions of RCD tester may be calibrated, including: trip time, AC residual current, residual pulsating DC current with a superimposed DC current and AC residual current in a stepwise ramp-up pattern. The system uses an adjustable earth-current leakage relay, which provides an easy way to test a wide range of trip time and residual current. The in-house developed delay circuit supports the testers designed for S-type RCD testing. A bank of non-inductive resistors is available for accurate and traceable calibration of residual current. Details of the developed system and the associated uncertainty evaluation are presented in the paper.